1852 Del. Rev. Stat 215 - (:unkn) unknown (My University, 1852)
Tit. 10, ch. 73, § 27: to provide for the weighing of hay, and for the measuring, or weighing, of coal, lime, grain, or any other matter sold in the said city; to regulate the storage of gunpowder, or any other dangerously combustible matter.§
Keywords: GUNPOWDER - STORAGE